2019
DOI: 10.3390/rs11182089
|View full text |Cite
|
Sign up to set email alerts
|

Re-Discovering Ancient Landscapes: Archaeological Survey of Mound Features from Historical Maps in Northwest India and Implications for Investigating the Large-Scale Distribution of Cultural Heritage Sites in South Asia

Abstract: Incomplete datasets curtail the ability of archaeologists to investigate ancient landscapes, and there are archaeological sites whose locations remain unknown in many parts of the world. To address this problem, we need additional sources of site location data. While remote sensing data can often be used to address this challenge, it is enhanced when integrated with the spatial data found in old and sometimes forgotten sources. The Survey of India 1” to 1-mile maps from the early twentieth century are one such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 54 publications
(69 reference statements)
1
25
0
Order By: Relevance
“…The systematic documentation of mound features visible on historic maps will make it possible to filter and query the data set at a later stage to select specific types of features, create thematic maps, quantify aspects of those features, and perform statistical analyses. Although substantial numbers of archaeological sites have already been documented across northwest India [75][76][77][78], attempts to conduct systematic survey using historic maps as a key data source has shown that the currently 'known' sites represent only a fraction of the actual archaeological settlements in the region [84][85][86][87][88]. Although a large number of the almost 9000 mound features visible in the historical maps that have been studied are likely to be natural, if even one tenth of them turn out to be archaeological sites, then the number of known sites in the region will increase dramatically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic documentation of mound features visible on historic maps will make it possible to filter and query the data set at a later stage to select specific types of features, create thematic maps, quantify aspects of those features, and perform statistical analyses. Although substantial numbers of archaeological sites have already been documented across northwest India [75][76][77][78], attempts to conduct systematic survey using historic maps as a key data source has shown that the currently 'known' sites represent only a fraction of the actual archaeological settlements in the region [84][85][86][87][88]. Although a large number of the almost 9000 mound features visible in the historical maps that have been studied are likely to be natural, if even one tenth of them turn out to be archaeological sites, then the number of known sites in the region will increase dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…The viability of the categorisation outlined here has been tested in the field over several field seasons [84][85][86][87] (Figure 12), and the detailed results of this analysis are the subject of a separate paper [88]. To facilitate the process of ground-truthing, each feature location was included in a field survey table and assigned Historical Feature Identification Numbers (hf_id), which will be used to create a comprehensive listing of preserved and potentially lost archaeological sites.…”
Section: Testing the Archaeological Viability Of The Identification Omentioning
confidence: 99%
See 1 more Smart Citation
“…2600-1900 BC). In Cholistan, there appears to have been an increase in settlement numbers and in settled area (Mughal 1997;Petrie and Lynam 2020), and in northwest India, archaeological surveys have revealed a significant reduction in the number of settlements surrounding Rakhigarhi (Green and Petrie 2018;Green et al 2019;. The concurrent growth of urban settlement area suggests that a subset of older settlements may have absorbed population from others that were abandoned in close proximity.…”
Section: Settlement Growth and Nucleationmentioning
confidence: 99%
“…Despite the obvious problems involved in extrapolating interpretations extracted from very specific geographical and temporal frameworks, small-scale analyses are an important mechanism for understanding the parameters in play for large-scale dynamics. Elsewhere we have addressed the nature of the map sources and their potential for types of analysis performed here, but in a larger scale for the detection of archaeological sites [28,52]. The specific case of DG Khan presented here allows us to address in more detail the significance of historical morphodynamics as one of the many interpretation filters that can be used when observing the available prehistoric settlement distribution maps of the Indus basin.…”
Section: River Morphodynamics Settlement Patterns and Archaeologicalmentioning
confidence: 99%